A Schur method for the solution of the matrix Riccati equation - Mohsen Razzaghi (International Journal of Mathematics and Mathematical Sciences)
This paper is concerned with an analytic solution of the finite-time matrix Riccati equation. The solution to the Riccati equation is given in terms of multiple of two matrices. These matrices are found using a Schur-type decomposition for Hamiltonian matrices. Simple examples illustrating the method are presented.